2000
DOI: 10.1063/1.481839
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally inelastic collisions of OH(X 2Π)+Ar. I. State-to-state cross sections

Abstract: Inelastic collisions of OH(X 2Π)+Ar at an energy of 746 cm−1 have been studied in a crossed molecular beam experiment. The OH(X 2Π) radicals were prepared in the v=0, Ω=32, J=32, f state by hexapole state selection. Parity-resolved integral state-to-state cross sections for rotational excitation have been determined up to the Ω=32, J=92 and Ω=12, J=52 states. A strong preference is found for spin–orbit manifold conserving transitions to final states of e symmetry. The experimental results are compared to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…Collisions populating the F 1 (3/2e) level were most likely. Within the F 1 (5/2) level, collisions populating the lower Λ-doublet component of e parity were favored, consistent with findings of other 2 Π-rare gas systems (28,29 ). For the F 1 (3/2e) and the F 1 (5/2e/f ) levels, the transition probabilities were almost constant at higher collision energies.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Collisions populating the F 1 (3/2e) level were most likely. Within the F 1 (5/2) level, collisions populating the lower Λ-doublet component of e parity were favored, consistent with findings of other 2 Π-rare gas systems (28,29 ). For the F 1 (3/2e) and the F 1 (5/2e/f ) levels, the transition probabilities were almost constant at higher collision energies.…”
supporting
confidence: 73%
“…In a crossed beam set-up, rotationally inelastic scattering between state-selected OH radicals (X 2 Π 3/2 , v = 0, J = 3/2, f (27 ), referred to hereafter as F 1 (3/2f )) and Xe atoms is studied throughout the 0.14 to 1.14 kcal/mol (50 to 400 cm −1 ) region, with an overall energy resolution of ∼ 0.03 kcal/mol (13 cm −1 ). We chose the OH-rare gas system because, at higher collision energies, rotationally inelastic collisions have been studied for this system in great detail, both experimentally and theoretically; state-to-state cross-sections and the effects of molecular orientation have been determined (28,29 ). The energy range covered in the present study encompassed the energetic thresholds for inelastic scattering down to the lowest rotational levels of OH.…”
mentioning
confidence: 99%
“…Early calculations [17,18] on rotationally inelastic scattering of N 2 molecules with He atoms have shown that resonances occur at low collision energies, but the experimental verification of these predictions was not yet possible. Collisions of OH(X 2 Π) with rare gases have emerged as paradigms of scattering of an open-shell molecule with an atom [13,15,[19][20][21][22][23][24]. The OH-rare gas systems are good candidates for the observation and analysis of resonances in rotationally inelastic collisions because the collision energy can be reduced by Stark deceleration of the OH beam.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of inelastic scattering with Ar concentrated mostly on NO, [8][9][10][31][32][33][34][35][36][37][38][39] OH, 18,21,22,24 and HCl, 40 although scattering of a polyatomic molecule with Ar has been explored in the case of NH 3 . 41,42 Molecular nitrogen was previously used as a collider in studies of the inelastic scattering of HCl.…”
Section: Introductionmentioning
confidence: 99%
“…6 This body of work extended the scope of inelastic scattering of labile free radicals, which had previously concentrated on collisions of diatomic radicals with atomic species. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A recent article by Dagdigian reviewed collisional energy transfer calculations for small hydrocarbon intermediates 26 and highlighted computational studies of integral cross sections for collisions of methylene (CH 2 ) 27,28 and methyl radicals. 5,28,29 The methyl radical is also the first polyatomic free radical to be slowed in a Zeeman decelerator using a pulsed magnetic field, 30 opening up new possibilities to study inelastic and reactive scattering at very low collision energies.…”
Section: Introductionmentioning
confidence: 99%